TEACHER CONSTRAINTS IN IMPLEMENTING AUTHENTIC ASSESSMENT OF GEOGRAPHY CURRENTS IN SMA NEGERI BANDAR LAMPUNG CITY - Nur Amanatun; Sugeng Widodo; Dian Utami; Annisa Salsabilla (Journal Learning Geography, 2022)
This study aims to identify and describe the obstacles faced by geography teachers in conducting authentic assessments, namely the geography teachers' understanding of authentic assessment, authentic assessment instruments, time allocation, and facilities and infrastructure. The method used is descriptive qualitative method using a narrative study strategy. The subjects of this study were teachers of geography at SMA Negeri 3 Bandar Lampung, SMA Negeri 10 Bandar Lampung, and SMA Negeri 14 Bandar Lampung. Data collection using observation techniques, interview techniques, and documentation techniques. The instruments in this study were observation guidelines, interview guidelines, and documentation guidelines. Data analysis used descriptive analysis techniques without using statistical formulations. The results of the study show that (1) Understanding of authentic assessment is not an obstacle in the implementation of authentic assessment. (2) The assessment instrument has not yet reached the implementation of an authentic assessment completely regarding affective assessment. (3) The time allocation has not yet reached the complete authentic assessment of affective assessment and cognitive assessment. (4) The facilities and infrastructure provided by the school are sufficient so that teachers can easily use the facilities and infrastructure to support learning activities. Facilities are an obstacle in the implementation of authentic assessments.